Embolic Stroke due to a Common Carotid Artery Thrombus in a Young Patient with Severe Iron-Deficiency Anemia without Thrombocytosis - David Roshal (Case Reports in Neurological Medicine)
This case report describes a 41-year-old previously healthy male who presented with stuttering transient ischemic symptoms and radiographic evidence of a left common carotid artery thrombus as well as acute and subacute ischemic infarcts in the left middle cerebral artery territory. An exhaustive stroke work-up did not provide a plausible etiology for his symptoms. His complete blood count and iron studies, however, revealed evidence of severe iron-deficiency anemia without reactive thrombocytosis. His stool guaiac test was positive. He was discharged home on oral antithrombotic agents and aggressive iron replacement therapy with a plan for repeat vascular imaging in 3 months and a colonoscopy. This case report suggests that severe iron-deficiency anemia with or without reactive thrombocytosis should be viewed as a possible hematologic condition associated with thrombotic tendencies and a risk factor for ischemic stroke, especially in young adults. Aggressive iron supplementation and short-term antithrombotic therapy with follow-up vascular imaging are a reasonable treatment for these patients.